Hypnoteaching Learning Theory Analysis in the Learning Process - Fathul Rahma; Neviyarni Neviyarni (Indonesian Institute for Counseling, Education and Theraphy, 2021)
Hypnosis is the art of interaction that influences someone by altering their level of awareness. Not only is hypnosis effective for resolving physical and psychological difficulties, but it can also be used in an attempt to optimize the learning process. Hypnosis is known as hypno-teaching in the learning process. Hypnosis is known as hypnoteaching in the learning process. The secret to the hypnoteaching technique is how teachers can internally and externally create a supportive learning atmosphere. They will also believe the learning process is enjoyable when relaxation is in learning, and when in a relaxed class, it is guaranteed that students will easily understand the material provided by the instructor.In essence, teachers are expected to be able to hypnotize students in this hypnoteaching process, this hypnosis attempts to put students into a calm, secure and quiet environment so that students can easily embrace any content and moral messages communicated by the instructor.